1997
DOI: 10.1063/1.365380
|View full text |Cite
|
Sign up to set email alerts
|

Passivation effect of silicon nitride against copper diffusion

Abstract: The use of Cu in ultralarge scale integrated ͑ULSI͒ conductors has resulted in the need to prevent Cu diffusion. We evaluated the passivation effect of plasma-enhanced chemical-vapor-deposited silicon nitride ͑PECVD-SiN͒ using secondary ion mass spectrometry and atomic absorption spectrometry. From these measurements, it was found that a large amount of Cu diffused through PECVD-SiN films during the heat treatments of the metallization process, probably due to the rapid diffusion paths along the microdefects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…Based on these various methods, PECVD a-SiN:H has been shown to be an excellent Cu diffusion barrier. 36,37,73,75 Similar tests have also shown that a-SiC:H 59,60,64 and a-SiCN:H 44,45 can perform equivalently to a-SiN:H as Cu diffusion barriers with reduced values of dielectric permittivity as low as 4.2-4.9. 276,277 Recent studies have also indicated that dense a-SiCO:H dielectrics can also serve as Cu diffusion barriers with k values as low as 3.5.…”
Section: -122mentioning
confidence: 73%
See 3 more Smart Citations
“…Based on these various methods, PECVD a-SiN:H has been shown to be an excellent Cu diffusion barrier. 36,37,73,75 Similar tests have also shown that a-SiC:H 59,60,64 and a-SiCN:H 44,45 can perform equivalently to a-SiN:H as Cu diffusion barriers with reduced values of dielectric permittivity as low as 4.2-4.9. 276,277 Recent studies have also indicated that dense a-SiCO:H dielectrics can also serve as Cu diffusion barriers with k values as low as 3.5.…”
Section: -122mentioning
confidence: 73%
“…This is a particularly germane question as the 2013 ITRS projects the thickness of the DB in a low-k/Cu interconnect will need to be only 1-2 nm thick in the next decade. 107 Unfortunately, early studies of the Cu diffusion barrier performance of a-SiN:H DB materials utilized relatively thick (>=100 nm) films, 37,73,75 and more recent studies of low-k DB materials have focused on evaluating Cu and H 2 O barrier performance at thicknesses of 30-100 nm. Only a few studies have attempted to investigate the ultimate limits in terms of DB thickness scaling.…”
Section: Current Status Of Low-k Db/ccl/es Materials and R And Dmentioning
confidence: 99%
See 2 more Smart Citations
“…A suitable diffusion barrier is crucial to suppress the diffusion and reaction taking place between copper and silicon at low temperatures for realizing thermally stable Cu/Si contact systems in current ULSI technology. For the material used as a diffusion barrier, it is required that the barrier should prevent the undesired diffusion and/or reaction, and also should be sufficiently low in resistivity [1,2]. Refractory metal binary and ternary nitrides are widely recognized as an attractive class of materials which can be used as diffusion barriers in metal-semiconductor contacts [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%